The 'thinking aloud' process: a way forward in social work supervision. Issue 1 (2nd January 2019) - Rankine, Matt
ABSTRACT: Within current neoliberal discourses, critical reflection provides opportunity for innovation in social work practice. This article describes a thinking aloud process used with supervisor–supervisee dyads in community-based child welfare social work to assist critical reflection via the use of open-ended questioning and inquiry. The strength of thinking aloud permitted a deeper appreciation of how the supervision session is utilised to reflect on practice and provided a learning tool within supervision. The feedback from the dyads concurred that thinking aloud assisted in stimulating reflection, developing solutions to the key issues discussed, and was transformative in recognising areas for future development. The process of thinking aloud supports the opportunity and space for the supervisor and supervisee to articulate meaning, critically develop insight, reconstruct, and transport this into future practice. Thinking aloud offers an example of how knowledge can be co-constructed by practitioners within practice and critical reflection captured within qualitative research approaches.